Katekisasi Pranikah Sebagai Parenting Education di Jemaat GKE Hosana Buntut Bali Kabupaten Katingan - Silipta (Institut Agama Kristen Negeri Palangka Raya, 2023)
The study aims to analyze the form of the pattern of implementation of premarital catechization in the Hosana GKE Buntut Bali congregation, Malan Island district, Katingan Regency. Methods used with a qualitative approach. The results of the study revealed that first, the implementation of premarital catechization in the Hosanna GKE Buntut Bali congregation was carried out ahead of the confirmation of marriage at the GKE Hosanna Buntut Bali church. Second, the meaning of premarital catechization in the GKE Buntut Bali congregation that for the church as a tradition and church regulation to provide teaching for adults before the confirmation of marriage so that the bride and groom are able to carry out the mandate as mature and morally responsible members of the church for marriage so as to become witnesses of Christ in the midst of the world through marriage. Third, the obstacles to the implementation of premarital catechization in the Hosana GKE Buntut Bali congregation, there are obstacles that occur in the implementation of premarital catechization from various parties such as: from the bride and groom who come from different regions and work factors. There are also brides-to-be who come from other faiths. On the part of the church, it is difficult to use what method is used to adjust to the material that is standard for the bride and her family with different backgrounds. Thus causing the church to give priority to the implementation of the marriage confirmation procession. Penelitian bertujuan untuk menganalisis bentuk pola pelaksanaan katekisasi pranikah di jemaat Hosana GKE Buntut Bali kecamatan Pulau Malan Kabupaten Katingan. Metode yang digunakan dengan pendekatan kualitatif. Hasil penelitian menungungkapkan bahwa pertama, pelaksanaan katekisasi pranikah di jemaat Hosana GKE Buntut Bali dilakukan menjelang peneguhan nikah di gereja GKE Hosana Buntut Bali. Kedua, makna katekisasi pranikah di jemaat GKE Buntut Bali bahwa bagi gereja sebagai sebuah tradisi dan peraturan gereja untuk memberikan pengajaran bagi orang dewasa menjelang peneguhan nikah sehingga calon mempelai mampu mengemban amanat sebagai anggota gereja yang dewasa dan bertanggung jawab secara moral atas pernikahan sehingga menjadi saksi Kristus di tengah dunia melalui pernikahan. Ketiga, kendala pelaksanaan katekisasi pranikah di jemaat Hosana GKE Buntut Bali, terdapat kendala yang terjadi pada pelaksanaan katekisasi pranikah berasal dari berbagai pihak seperti: dari pihak mempelai yang berasal dari daerah yang berbeda dan faktor pekerjaan. Terdapat pula calon mempelai yang berasal dari kepercayaan lain. Dari pihak gereja, kesulitan menggunakan metode apa yang digunakan menyesuaikan dengan materi yang baku pada calon mempelai dan keluarganya dengan latar belakang yang berbeda. Sehingga menyebabkan pihak gereja lebih mengutamakan pada pelaksanaan prosesi peneguhan nikah.